2012
DOI: 10.2138/am.2012.4020
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure refinements of borate dimorphs inderite and kurnakovite using 11B and 25Mg nuclear magnetic resonance and DFT calculations

Abstract: Borate minerals composed of [Bφ 3 ] triangles and/or [Bφ 4 ] tetrahedra (φ = O or OH) commonly exhibit complex polymerizations to form diverse polyanion groups. High-resolution solid-state magic angle spinning (MAS) 11 B and 25 Mg NMR spectroscopy at moderate to ultrahigh magnetic fields (9.4, 14.1, and 21.1 T) allows for very accurate NMR parameters to be obtained for the borate dimorphs, inderite, and kurnakovite, [MgB 3 O 3 (OH) 5 ·5H 2 O]. Improved agreement between experimental results and ab initio dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(57 citation statements)
references
References 30 publications
(41 reference statements)
4
53
0
Order By: Relevance
“…4,5 As such, the popularity of DFT calculations has in recent years formed a link between NMR and crystallography, leading to the formalization of "NMR crystallography". [9][10][11][12][13] For example, high-resolution 11 B magic angle spinning (MAS) NMR spectra of borate minerals such as ulexite and probertite have been obtained at high and ultrahigh magnetic fields (14 and 21 T). 7,8 Due to recent advances in NMR techniques as well as progress in quantum mechanical theoretical calculations, interest in 11 B NMR for determination of local structural characteristics in borates has been rekindled.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 As such, the popularity of DFT calculations has in recent years formed a link between NMR and crystallography, leading to the formalization of "NMR crystallography". [9][10][11][12][13] For example, high-resolution 11 B magic angle spinning (MAS) NMR spectra of borate minerals such as ulexite and probertite have been obtained at high and ultrahigh magnetic fields (14 and 21 T). 7,8 Due to recent advances in NMR techniques as well as progress in quantum mechanical theoretical calculations, interest in 11 B NMR for determination of local structural characteristics in borates has been rekindled.…”
Section: Introductionmentioning
confidence: 99%
“…3-6 11 B NMR parameters in borates and borosilicates, however, generally show limited variations and, hence, have been thought to be incapable of providing structural information beyond the first shell. [11][12][13] Although these borates with the ijB 5 O 6 IJOH) 6 ] 3− polyanion as the fundamental building block (FBB) (Fig. [9][10][11][12][13] For example, high-resolution 11 B magic angle spinning (MAS) NMR spectra of borate minerals such as ulexite and probertite have been obtained at high and ultrahigh magnetic fields (14 and 21 T).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting here that theoretical studies of hydrogen bonding can provide important information with a higher degree of precision then that available from X-ray diffraction measurements, especially for minerals that do not form high-quality crystals (Milman and Winkler 2001;Zhou et al 2012). It is also the task of the present work to compare the results of experimental and theoretical studies of the hydrogen bonding system in euchroite in order to investigate their complementarity and reliability.…”
Section: Introductionmentioning
confidence: 95%
“…In general, the chemical shift for the tetra-coordinated boron resonance reflects the distribution of the second-nearest neighbor cation (B or Si). [29], borosilicate glass [30] and tourmaline [31] have been reported as 1.29, 0.0, and −0.1 ppm, respectively. Angeli et al [30] and Lin-Shu et al [32] have been reported that tetra-coordinated boron in borosilicate glass has a chemical shift near 0 ppm and a structure of BO-B*-(OSi) 3 .…”
Section: Chemical Form Of Boron In the Precipitatesmentioning
confidence: 99%